U1-U2 snRNPs interaction induced by an RNA complementary to the 5' end sequence of U1 snRNA. - Daugeron, M C (1992)
Several lines of evidences indicate that U1 and U2 snRNPs become interacting during pre-mRNA splicing. Here we present data showing that an U1-U2 snRNPs interaction can be mediated by an RNA only containing the consensus 5' splice site of all of the sequences characteristic of pre-mRNAs. Using monospecific antibodies (anti-(U1) RNP and anti-(U2) RNP), we have found that a tripartite complex comprising U1 and U2 snRNPs is immunoprecipitated in the presence of a consensus 5' splice site containing RNA, either from a crude extract or from an artificial mixture enriched in U1 and U2 snRNPs. This complex does not appear in the presence of an RNA lacking the sequence complementary to the 5' terminus of U1 snRNA. Moreover, RNAse T1 protection coupled to immunoprecipitation experiments have demonstrated that only the 5' end sequence of U1 snRNA contacts the consensus 5' splice site containing RNA, arguing that U2 snRNP binding in the tripartite complex is mediated by U1 snRNP.